Fermentação alcoólica a partir de caldos ozonizados de diferentes etapas do processo da indústria sucroalcooleira - Ribeiro, Luzidelson Baracho (2017)
Brazil is the world's largest producer of sugarcane, the largest producer and exporter of sugar and the second largest producer of ethanol. The most commonly used method for the clarification of sugarcane juice is the conventional one, where sulfur dioxide, which is a toxic and polluting gas, is used. In view of the requirements of the world market with regard to food safety, alternative technologies for broth treatment have been sought. Ozone is currently used by twelve plants in Brazil, among them the Monte Alegre Plant, which is the pioneer in this technology. The objective of this work was to verify the influence of the clarification of the cane juice by ozonation in alcoholic fermentation, from musts composed of broths of different stages of the industrial process: mixed broth, clarified broth, evaporated broth and final honey. The work was carried out in partnership with the Monte Alegre plant. The fermentations were conducted under temperature and orbital agitation at 32 °C and 150 rpm, and time of 12 hours. The broths were collected from the process, as well as the yeast, which was the same propagated in the plant. A physical-chemical characterization of the broths was carried out, the influence of the initial concentrations of the substrate in the yeast propagation process was verified, the influence of the initial concentrations of substrate and of the cells in the alcoholic fermentation, and the fermentation kinetics for the different types of musts. In the propagation study, an initial cell concentration of 2.0 g.L-1 was used, and the must with 10 °Brix substrate concentration presented the best results, for a time of 7 hours, with a cell concentration of 11.6 g.L-1. In order to verify the influence of the initial concentration of substrates and cells in the alcoholic fermentation, from factorial planning and response surface, a maximized ethanol production was obtained for substrate concentration ranges between 13 and 20 ºBrix and cell concentration between 24 and 34 g.L-1. The condition of 13 ºBrix and 30 g.L-1 was adopted for the study of the kinetics of ethanol production in the different musts. Analyzes of reducing sugars and ethanol were carried out and the results obtained for the rates of substrate consumption, in g.L1.h-1, were: 7.28 ± 2.3 for the mixed broth, 6.78 ± 1.2 for the clarified broth, 6.34 ± 1.4 for the evaporated broth and 7.32 ± 1.6 for the final honey. The yields in ethanol, in g.L-1.h-1, were: 2.93 ± 0.81 for the mixed broth, 2.70 ± 0.57 for the clarified broth, 2.50 ± 0.51 for the broth evaporated and 2.70 ± 0.49 for the final honey. Through the statistical analysis of the results, it can be concluded that the types of treatments used in the musts composition, as well as the clarification system by ozonation, did not significantly influence the alcoholic fermentation. The greatest variations were observed for the different days of production, which is related to the variations of the raw material processed and the oscillations of the industrial process.